Charcoal income as a means to a valuable end: Scope and limitations of income from rural charcoal production to alleviate acute multidimensional poverty in Mabalane district, southern Mozambique. (September 2017) - Vollmer, Frank; Zorrilla-Miras, Pedro; Baumert, Sophia; Luz, Ana Catarina; Woollen, Emily; Grundy, Isla; Artur, Luis; Ribeiro, Natasha; Mahamane, Mansour; Patenaude, Genevieve
Highlights: Analysis of the contribution of charcoal income to acute poverty alleviation. 59% of non-monetary poor among charcoal producers are living in acute poverty. Charcoal income increases resistance to impoverishment. Charcoal income is not a statistically significant determinant of acute poverty. Findings show that charcoal income does not sufficiently alleviate acute poverty. Abstract: The charcoal industry is among the most important semiformal economic sectors in Sub-Saharan Africa and a key cash income source for local households who produce it. This has intensified the debate as to the role of income from charcoal production in the alleviation of rural poverty. While in a number of cases charcoal production has been identified as a potential alleviator of monetary poverty, this paper takes as its departure point a lack of analysis on the effect of charcoal income on acute multidimensional poverty (AMP). This is understood as the inability of household members to meet minimum national and international standards and core functionings . This study used primary data from an important charcoal supplying region in southern Mozambique (N = 312). The Alkire-Foster method was used to aggregate AMP in nine composite indicators. Generalised linear models were used to assess the marginal effect of charcoal income on AMP, controlling for other determinants. Our findings show a high intensity (67.7%) and prevalence of AMP (0.429) in the study area (n = 261). 59% of the identified non-monetary poor from charcoal making are identified as acute multidimensionally poor. Charcoal income is found to be positively correlated with valuable household assets, and charcoal production increases the resistance to impoverishment in certain circumstances. However, charcoal income was not found to be a statistically significant determinant of AMP, even for the most productive charcoal makers. This highlights the enormous barriers both producers and non-producers of charcoal alike face in this region in order to overcome AMP. Our findings thus challenge the perception that charcoal income can sufficiently alleviate poverty, particularly when a multidimensional perspective is adopted. Reductions and eventual eliminations of AMP require a concentrated cross-sectional whole-of-government approach to tackle poverty in its multidimensional breadth and complexity, while attempts at making the charcoal industry more inclusive and equitable should be accelerated.